AB1257-HPR Project to Develop Support Materials for Teaching and Training in Rheumatology Using Icts: Two Years of Experience at the Rheumatology Service of the Complexo Hospitalario Universitario de a Coruña. (9th June 2015) - Freire, M.; Gromaz, J.; Diaz, M.; Alonso, E.; Aspe, B.; Atanes, A.; Bejerano, M.; Blanco, F.; Graña, J.; Lopez, C.; Oreiro, N.; Pinto, J.; et al.
Abstract : Background: The development of the internet and social media in everyday life has revolutionized the methods of data exchange as well as the search for information on the part of students and health professionals. Medical educators/teachers should not ignore this fact. Objectives: To develop a reliable channel of informatiom To train health professionals in the learning of rheumatology exploration/research and basic knowledge of musculoskeletal diseases To develop a reliable channel of informatio Methods: We have created a channel [of communication] - "CHUAC Rheumatology" - on the youtube webpage in order to upload and host teaching material. Illustrative videos of short duration have been recorded using an electronic tablet or camcorder. They have been edited with a very simple program. Two playlists have been created. The first one contains a whole set of videos on exploration, whereas the second one compiles basic lesson plans on rheumatology, including: Anatomical background aimed at improving the knowledge of rheumatic diseases, general principles of diagnosis - anamnesis, laboratory, radiology, management of osteoarthritis, back pain, osteoporotic vertebral fracture and knee arthrocentesis. Results: The channel was created on January 14, 2013. There are 37 videos hosted. We have had 71, 993 visits which amount a total of 3578 hours of viewing and a rate of average audience retention of 3 minutes on each visit. The main searching source is the web youtube (91%). The material has been seen mainly from Spain (40%) and Mexico (20%). We have 468 subscribers and we have received 303 messages of satisfaction ("Like"). If we analyze the five main locations of viewing, we come across a striking fact: in South America the material is mainly seen by students and health professionals that are between 18 and 34 years (between18 and 24 years (39-49%) and between 25-34 years (30-42%)). In Spain, however, the material is viewed and accessed in a fairly uniform way, from students that are 18 to adults that are 64 years old (15-16%), with an incidence peak between 25 and 34 (27%) and 45-54 (24%). In addition, the opinion of MIR students and of those who rotate around our service is very positive as they have teaching materials prior to rotation around our service. Conclusions: In our opinion, this experience is useful to facilitate the learning of process of students and health professionals, and to improve the visibility of our hospital. The internet represents an important aid to support teaching and training needs and, therefore, we should make use of it. Furthermore, it is important to improve the digital skills aimed at teaching and training. Disclosure of Interest: None declared